A MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMA NEGERI 1 BENGKULU SELATAN BERBASIS MULTIMEDIA - Lafini, Ugesti Dwi; Sapri, Sapri (Jurnal Media Infotama, 2021)
One of the advances in information technology in the field of education today is learning media. The more technological conveniences offered, the more progress in science and technology becomes increasingly sophisticated. This learning media was prepared at the beginning of semester 2, meetings 1 to 7 to be used throughout one semester of class XI. The data collection methods used in preparing this learning media are observation, interviews and literature. The media displayed specifically discusses the care of Muslim bodies (bathing the body, shrouding the body, praying for the body, burying the body). From the results of the analysis and discussion, it can be concluded that the learning media for Islamic Religious Education at SMA Negeri 1 South Bengkulu using Macromedia Flash 8 is very interesting.